Novel Potentiometric Sensors of Ion Imprinted Polymers for Specific Binding of Yttrium(III) - Huang, Shuiying; Luo, Fengxian; Lai*, Xiaoqi (Asian Journal of Chemistry, 2014)
A novel potentiometric sensor of yttrium(III) ion was designed by embedding the yttrium(III) ion-imprinted polymer (Y3+IIP) particles in poly(vinyl alcohol) matrix. The (Y3+IIP) was prepared by using a single pot method. The sensor shows a Nernstian response for yttrium(III) over a wide concentration range (5 × 10-7 to 5 × 10-2 M) with a slope of 29.8 mV per decade. The detection limit can reach as low as 3 × 10-7 M. The proposed sensor has a fast response time (less than 10 s) and offers a high selectivity with respect to several alkali, alkaline earth and transition metal ions and can be used in a pH range of 6.5-8.5. This sensor was applied as an indicator electrode in the potentiometric titration and has been successfully used for the determination yttrium(III) in the yttrium-aluminium alloy sample with direct potentiometry.